Excessive anticoagulation identified by emergency medical service through point-of-care coagulometry - Beynon, Christopher; Erk, Angelina G.; Popp, Erik; Mohr, Stefan; Heiser, Felix (Signa Vitae, 2015)
Bleeding because of excessive anticoagulation is a well-recognized complication of coumadin therapy. In cases of potentially life-threatening bleeding such as intracranial haemorrhage, reversal of anticoagulation should be carried out as...